The Concept of Digitalization-based Performance Management In An Effort to Improve Employee Performance During the Covid-19 pandemic in Village-Owned Enterprises (BUMDES) throughout Buleleng Regency - Adnyana, Putu Agus (International Journal of Social Science and Business, 2021)
The purpose of this study is to determine employee performance through the concept of work management and digitalization as the main keys to improving the performance of BUMDES employees in Buleleng Regency. The concept of performance management is the employee’s activities and work results in line with organizational goals. So that it contributes to improving the performance of BumDes employees. The study population was all active BumDes in Buleleng Regency. Sampling in this study using random sampling technique. The data analysis technique used in this research is the Component based SEM, Partial Least Square (PLS) analysis method. The results showed that the concept of work management has an effect on digitization and employee performance.